Should Advanced Countries Adopt a Fiscal Responsibility Law? - Lienert, Ian (International Monetary Fund, 2010)
Fiscal Responsibility Laws (FRLs) appear to be more popular in middle-income countries than advanced countries, even though their success is limited. The reasons why few advanced countries have a FRL include: the existing legal framework for the budget system is adequate; supranational rules and political agreements in EU countries; failed attempts to include quantitative fiscal rules in laws; lack of consensus or interest in attaining the goals of FRL-type legislation; and lack of need for a law to regulate fiscal transparency, accountability and macro-fiscal stabilization. Without commitment to fiscal discipline, adoption of a FRL may not contribute to attaining fiscal consolidation goals